Braiding Rivers: State of the Art and Future Challenges. Issue 42 (21st October 2014) - Bertoldi, Walter; Recking, Alain; Surian, Nicola
<x xml:space="preserve">Abstract</x> Eleven years after the last Braided Rivers Conference in Birmingham, England, a group of 47 scientists from 11 countries met at le Domaine de Sainte Croix, France, to discuss the current state of knowledge and future research directions for braided rivers. Several core themes and research challenges arose from the 5‐day workshop.